Synergistic reinforcement effect of aramid nonwoven fabrics and PVDF on mechanical and damping properties of bismaleimide matrix composites. (December 2015) - Ni, Nannan; Wen, Yuefang; He, Delong; Yi, Xiaosu; Wang, Chengcheng; Xu, Yahong
Abstract: A new type of structural damping composite was prepared by interleaving aramid nonwoven fabrics (ANF) modified with semi-crystalline polyvinylidene fluoride (PVDF) between carbon-fibre-reinforced bismaleimide (BMI) laminae. The co-cured composite exhibited an increase of 108% and 2.72% in loss factor and flexural modulus, respectively, compared with the original carbon-fibre-reinforced BMI composite. The damping behaviour of the co-cured composites was experimentally investigated using the single cantilever beam test and dynamic mechanical analysis. Furthermore, the composite interlaminar shear strength and flexural strength and modulus were also investigated. The results indicated that the composite interleaved with ANF/PVDF possessed higher flexural modulus and loss factor than the composites interleaved with ANF or PVDF films alone as a result of synergistic reinforcement of ANF and PVDF. Finally, the reinforcement mechanism of ANF/PVDF was investigated by analyzing the composite microstructure and the dynamical mechanical properties of ANF, PVDF, and ANF/PVDF interlayers.